Pengaruh Penggunaan Media Pembelajaran Baamboozle Terhadap Kemampuan Menulis Teks Eksposisi Pada Siswa Kelas X SMA Negeri 7 Medan Tahun Ajaran 2025/2026 - Nomi Simorangkir; Juni Agus Simaremare; Martua Reynhat Sitanggang Gusar (PGSD Universitas Muria Kudus, 2026)
This study aims to determine the effect of using the Baamboozle learning media on students' ability to write exposition texts in the tenth grade of SMA Negeri 7 Medan. This research employed a quantitative approach with an experimental method using a one-group pretest-posttest design. The population of this study consisted of all tenth-grade students of SMA Negeri 7 Medan, while the sample consisted of 34 students selected through simple random sampling. The research instrument used was a writing test in the form of pretest and posttest to measure students' ability to write exposition texts. The data were analyzed using descriptive statistical analysis and hypothesis testing with a t-test. The results showed that the average pretest score of students was 60,29 which was categorized as low, while the average posttest score increased to 81,61, which was categorized as good. The hypothesis testing results indicated that the t-count was higher than the t-table at the significance level of 0.05, meaning that the alternative hypothesis was accepted. Therefore, it can be concluded that the use of Baamboozle learning media significantly improves students' ability to write exposition texts. In addition, this learning media also increases students' engagement and motivation in the learning process.